Blue energy recovery in the Atacama Desert using electrochemical ion pumping devices: a Chilean perspective on salinity gradient energy - Galleguillos Madrid, Felipe M.; Salazar-Avalos, Sebastián; Bergendahl, Markus; Quispe, Javier; Toro, Norman; Casanueva-Yáñez, Galvarino; Soliz, Alvaro (Frontiers in Chemistry, 2025)
The growing global demand for clean and sustainable energy has intensified the development of novel technologies capable of harnessing naturally available resources. Among these, blue energy, referring to the power generated from the mixing of waters with different salinities, has emerged as a promising yet underutilized source. This perspective presents a comprehensive synthesis of recent advances in electrochemical harvesting systems, with a particular focus on Mixing Entropy Batteries (MEBs) as efficient, membrane-free devices for salinity gradient energy recovery. Unlike conventional approaches such as Reverse Electrodialysis (RED) and Pressure Retarded Osmosis (PRO), which depend heavily on ion-exchange membranes and complex infrastructure, MEBs offer simplified and scalable architecture suitable for harsh environments and industrial effluents. The use of LiCl-based electrolytes enables significant blue energy recovery, achieving energy densities of 38.2 mJ/cm2 and power densities of 13.8 μW/cm2, with excellent cycling stability. This system leverages the high solubility of LiCl (832 g/L) to create steep salinity gradients, utilizing LiFePO4/FePO4 as the cathode and Ag/AgCl as the anode, with no observable performance degradation over 100 cycles. This work analyzes alternative electrode materials, including Prussian Blue analogues (copper hexacyanoferrate CuHCF), MnO2, BiOCl, and polypyrrole, and explores their integration with unconventional water sources such as industrial brines, hypersaline reject streams, and treated wastewater, particularly within the resource-constrained context of the Atacama Desert. This manuscript consolidates experimental data, device designs, and comparative performance metrics, providing a critical framework for advancing blue energy technologies. It also underscores their potential role in circular economy models and off-grid renewable energy systems solutions.